Correction: Expanded scope of Griesbaum co-ozonolysis for the preparation of structurally diverse sensors of ferrous iron. Issue 58 (19th November 2021) - Chen, Jun; Gonciarz, Ryan L.; Renslo, Adam R.
Abstract : Correction for 'Expanded scope of Griesbaum co-ozonolysis for the preparation of structurally diverse sensors of ferrous iron' by Jun Chen et al., RSC Adv., 2021, 11, 34338–34342, DOI: ; 10.1039/d1ra05932g .